Glycine Betaine: A Potential Secondary Metabolite against Abiotic Stresses - Singh, Amantika; Singh, Pooja; Choudhary, Krishna Kumar (Journal of Pharmacy and Nutrition Sciences, 2022)
Abiotic stresses like temperature, water, salinity, ultraviolet (UV) radiations, heavy metals, etc., affect plants’ growth and yield. Despite these constraints, plants produce a variety of metabolites to maintain their survival. Primary metabolites, produced through crucial metabolic processes, are essential for plants survival. Additionally, secondary metabolites (SMs) are synthesized from primary metabolites and are mainly used as a defensive mechanism and a means of interacting with unfavorable environmental conditions. In addition to their defensive function in plants, SMs are significant in the pharmaceutical industry. Glycine betaine (GB) is a quaternary ammonium compound that belongs to a class of SMs, present in plants, animals, and microbes. It functions as a compatible solute and reflects potential bioactivity against various abiotic stresses like salinity, water, heat, heavy metals, UV radiations, etc. Due to high solubility and low viscosity, its accumulation is commonly observed in chloroplasts and plastids. The accumulation level generally depends on plant species, growth stage, exposure duration, and stress's nature. GB reduces oxidative stress and prevents the damaging of photosystems and other biomolecules under stressful conditions. It is important for maintaining the water potential and osmotic pressure of cells and hence functions as a potent osmolyte under salinity stress. Excessive production of ROS during temperature stress is responsible for damage to oxygen-evolving complexes, electron transport chains, and photosystems. In order to protect plants from these damages, GB activates the genes responsible for synthesizing heat shock proteins, glycoproteins, and antioxidants via various signaling pathways. GB alleviates the effect of water stress by maintaining the function of rubisco and calcium ion ATPase activity via crosstalk with Abscisic acid (ABA) and ethylene. GB supports the proper functioning of the ascorbate-glutathione cycle, superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase (antioxidative enzymes) to overcome various stresses. Phytohormones like salicylic acid (SA), jasmonic acid (JA), ABA, ethylene, and polyamines (PAS) coordinate well with GB via different signaling pathways to ensure plant protection under various abiotic stresses. The potential bioactivity of GB against various abiotic stresses in plants has been summarized in this review.